Translation and Psychometric Properties of the Arabic Version of Michigan Neuropathy Screening Instrument in Type 2 Diabetes - Maha T. Mohammad; Jennifer Muhaidat; Munther S. Momani; Lara Al-Khlaifat; Rasha Okasheh; Dania Qutishat; Emad Al-Yahya (Journal of Diabetes Research)
Objective. To translate the patient questionnaire section of the Michigan Neuropathy Screening Instrument (MNSI) into Arabic, examine the reliability of the translated version, and provide descriptive data on a sample of patients with type 2 diabetes. Methods. Researchers used the translation-back translation method to obtain MNSI Arabic. The test was then applied on 76 patients with type 2 diabetes. A subgroup of 25 patients answered MNSI Arabic twice to examine reliability. Results. The intraclass correlation coefficient was 0.87, revealing good reliability of MNSI Arabic. The most common symptoms patients complained of were numbness (62%), prickling feelings (57%), burning pain (47%), and pain with walking (46%). Conclusion. Similar to the original MNSI version, our study demonstrates that the Arabic version of the MNSI questionnaire is a reliable tool for screening the symptomatic neuropathy status in patients with type 2 diabetes. Availability of this tool in Arabic will provide valuable and easy-to-obtain screening information regarding diabetic peripheral neuropathy that may help delay its complications by promoting early management.